Meta-assembly of genomic associations to identify cattle fat depot candidate genes and pleiotropic effects - Junpeng Yao; Cynthia D.K. Bottema; Mehar Singh Khatkar (BMC Genomics)
Abstract Background Fat traits in cattle are considered important due to their contribution to beef eating quality and carcass economic value. Discovering the genes controlling fat traits in cattle will enable better selection of these traits, but identifying these genes in individual experiments has proven difficult. Compared to individual experiments, meta-analyses allow greater statistical power for detecting quantitative trait loci and identifying genes that influence single and multiple economically important fat traits. Results This meta-analysis study focussed on fat traits related to the major adipose depots in cattle (namely, carcass fat, intramuscular fat, internal fat, intermuscular fat, and subcutaneous fat) and was conducted using data from the Animal Quantitative Trait Loci (QTL) database. There were more Meta-QTL regions for intramuscular fat and subcutaneous fat (n = 158 and n = 55 regions, respectively) and far fewer for carcass fat and internal fat (n = 2 regions each). There were no Meta-QTL regions found for intermuscular fat. Of these 216 Meta-QTL regions, only 16 regions overlapped and affected two or more fat depots. The number of genes found for the fat depots was reflected in the size and number of the Meta-QTL regions (n = 20, 84, 1336 and 3853 genes for the carcass, internal, subcutaneous and intramuscular fat, respectively). The identification of these QTL allowed a more refined search for candidate genes. For example, the 232 genes in the Meta-QTL regions for carcass fat on BTA2, for intramuscular fat on BTA12, and the overlapping Meta-QTL regions on BTA2, BTA5, and BTA6 were readily screened, and 26 candidate genes were nominated based on their physiological roles using the GeneCards and DAVID databases. Conclusions The number of Meta-QTL regions for the various fat depots was relative to the number of associations in the database. However, the scarcity of overlapping Meta-QTL regions suggests that pleiotropic gene variants, which control multiple fat depots in cattle, are rare. The identification of candidate genes in the Meta-QTL regions will improve our knowledge of the genes with regulatory functions in adipose metabolism affecting meat quality and carcass economic value.